A review of workload-monitoring considerations for baseball pitchers - Dowling, B.; McNally, M. P.; Chaudhari, A. M. W.; Oñate, J. A. (Journal of Athletic Training, 2020)
Because of the unique demands of a pitch, baseball players have the greatest percentage of injuries resulting in surgery among high school athletes, with a majority of these injuries affecting the shoulder and elbow due to overuse from throwing. These injuries are believed to occur because of repeated microtrauma to soft tissues caused by the repetitive mechanical strain of throwing. Researchers and practitioners have suggested that baseball pitchers' workloads are a significant risk factor for injury in adolescent players, resulting in lost time and slowing of performance development. The purpose of our review was to investigate the current research relative to monitoring workload in baseball throwers and discuss techniques for managing and regulating cumulative stress on the arm, with a focus on preventing injury and optimizing performance in adolescent baseball pitchers.